Antimicrobial potential of haloalkaliphilic Nocardiopsis sp. AJ1 isolated from solar salterns in India. (3rd January 2019) - Adlin Jenifer, John Selesteen Charles; Michaelbabu, Mariavincent; Eswaramoorthy Thirumalaikumar, Chinnadurai Lelin; Jeraldin Nisha, Selva Raj; Uma, Ganapathi; Citarasu, Thavasimuthu
Abstract : Antagonistic haloalkaliphilic Nocardiopsis sp. AJ1 (GenBank JX575136.1), isolated and identified from the saline soil of Kovalam solar salterns was able to produce antimicrobial secondary metabolites and effectively suppressed several bacterial and fungal pathogens. The metabolite extracted from ethyl acetate precipitation suppressed the bacterial and fungal pathogens to the range between 2.14 and 20.14 mm and also controlled the shrimp killer virus WSSV by 83% than the control and significantly ( p  < 0.05) differed. GC‐MS analysis revealed that, the ethyl acetate precipitation contains pyrrolo (1, 2‐A(pyrazine‐1, 4‐dione, hexahydro‐3‐(2‐methylpropyl)‐) and actinomycin C2. Non ribosomal peptide synthetase (NRPS) was amplified by PCR with the amplicon size of 750‐800 bp length and further predicted the secondary structure by Iterative Threading Assembly Refinement (I‐TASSER) bioinformatics approach. I‐TASSER prediction helped to find out the secondary, 3‐D structure, and ligand binding sites. The top ten modelling concluded that, the NRPS gene is closely similar to surfactin synthesizing gene, surfactin A synthetase C (SRFA‐C). The findings revealed that, the active compounds from the secondary metabolites effectively suppressed the pathogenic bacteria, fungi, and virus and useful to develop antimicrobials.